Dedifferentiated and Undifferentiated Ovarian Carcinoma: An Aggressive and Molecularly Distinct Ovarian Tumor Characterized by Frequent SWI/SNF Complex Inactivation - Tessier-Cloutier, Basile; Kommoss, Felix K F; Kolin, David L; Němejcová, Kristýna; Smith, DuPreez; Pors, Jennifer; Stewart, Colin J R; McCluggage, W Glenn; Foulkes, William D; von Deimling, Andreas; Köbel, Martin; Lee, Cheng-Han (Modern pathology, 2024)
Dedifferentiated and undifferentiated ovarian carcinomas (DDOC/UDOC) are rare neoplasms defined by the presence of an undifferentiated carcinoma. In this study, we detailed the clinical, pathological, immunohistochemical, and molecular features of a series of DDOC/UDOC. We collected a multi-institutional cohort of 23 DDOC/UDOC and performed immunohistochemistry for core switch/sucrose nonfermentable (SWI/SNF) complex proteins (ARID1A, ARID1B, SMARCA4, and SMARCB1), mismatch repair (MMR) proteins, and p53. Array-based genome-wide DNA methylation and copy number variation analyses were performed on a subset of cases with comparison made to a previously reported cohort of undifferentiated endometrial carcinoma (UDEC), small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), and tubo-ovarian high-grade serous carcinoma (HGSC). The age of all 23 patients with DDOC/UDOC ranged between 22 and 71 years (with an average age of 50 years), and a majority of them presented with extraovarian disease (16/23). Clinical follow-up was available for 19 patients. Except for 2 patients, the remaining 17 patients died from disease, with rapid disease progression resulting in mortality within a year in stage II-IV settings (median disease-specific survival of 3 months). Eighteen of 22 cases with interpretable immunohistochemistry results showed loss of expression of core SWI/SNF protein(s) that are expected to result in SWI/SNF complex inactivation as 10 exhibited coloss of ARID1A and ARID1B, 7 loss of SMARCA4, and 1 loss of SMARCB1. Six of 23 cases were MMR-deficient. Two of 20 cases exhibited mutation-type p53 immunoreactivity. Methylation profiles showed coclustering of DDOC/UDOC with UDEC, which collectively were distinct from SCCOHT and HGSC. However, DDOC/UDOC showed an intermediate degree of copy number variation, which was slightly greater, compared with SCCOHT but much less compared with HGSC. Overall, DDOC/UDOC, like its endometrial counterpart, is highly aggressive and is characterized by frequent inactivation of core SWI/SNF complex proteins and MMR deficiency. Its molecular profile overlaps with UDEC while being distinct from SCCOHT and HGSC.
Keywords: nádorový supresorový protein p53; senioři; epiteliální ovariální karcinom; Brain Neoplasms; jaderné proteiny; ARID1B; SMARCA4; DNA Helicases; kolorektální nádory; Nuclear Proteins; SMARCB1; Middle Aged; DNA Copy Number Variations; Colorectal Neoplasms; DNA-helikasy; nádory vaječníků; mladý dospělý; Adult; Tumor Suppressor Protein p53; nádory endometria; Transcription Factors; Endometrial Neoplasms; Biomarkers, Tumor; Carcinoma; malobuněčný karcinom; transkripční faktory; undifferentiated ovarian carcinoma; Young Adult; ženské pohlaví; nádorové biomarkery; SWI/SNF; Humans; dědičné nádorové syndromy; methylation; lidé středního věku; nádory mozku; Neoplastic Syndromes, Hereditary; Carcinoma, Ovarian Epithelial; dospělí; variabilita počtu kopií segmentů DNA; Female; Aged; Ovarian Neoplasms; Carcinoma, Small Cell; lidé; karcinom